Dielectric Behaviour of Polyurethane Coatings Derived from Palm Oil Oleic Acid-Based Polyols -A Renewable Resource - Velayutham, T.S.; Abd Majid, Wan Haliza; Gan, S.N. (2012)
Dielectric relaxation spectroscopy (frequency range from 100Hz to 40 MHz) was used to examine molecular motion in polyurethane (PUR) derived from palm oil oleic acid-based polyols at room temperature. PUR was prepared by varying the oleic acid content in the polyol (28°c, 40°c and 65°c), while the NCO/OH ratio of PUR was varied to 1.2, 1.4 and 1.6. The effect of chemical contribution on dielectric behaviour of the samples was described. Dielectric parameters were in the range of 2.0 to 3.0 for real permittivity and 0.02 to 0.08 for imaginary permittivity, s". A Cole-Cole plot was fitted using the Havriliak-Negami model, and curve- fitting simulations were performed using Origin software program. A y-relaxation process was proposed as the probable mechanism for the dielectric behaviour of PUR. The dielectric constant and loss mechanism of the material were dependent on the NCO/OH ratio and the percentage of oleic acid content in the polyols used in synthesising PUR. The frequency-dependent conductivity of PUR materials zvas analysed using a Jonscher's power-law expression, and the plot exhibited a DC plateau and a frequency-dependent region.